Status quo of social cohesion in elderly patients with cancer and its influencing factors. - WANG Ruizhe; LI Mingyan; YANG Xueqin (Chinese Nursing Research, 2025)
Objective: To investigate the status quo of social cohesion in elderly patients with cancer and to analyze its influencing factors. Methods: A total of 172 elderly patients with cancer admitted to the oncology department of a tertiary grade A hospital in Jingmen city were selected as research subjects by convenience sampling methods from November 2023 to March 2024. The general information questionnaire, Social Cohesion Scale, Lubben Social Network Scale, and Activities of Daily Living were used for the survey. Results: The total score of social cohesion for 172 elderly patients with cancer was 22.59±6.91 points. Multiple linear regression analysis showed that the educational level, duration of illness, social network, and activities of daily living of elderly patients with cancer were important factors affecting their social cohesion, explaining 64.3% of the total variation. Conclusions: The social cohesion in elderly patients with cancer is poor. Clinical medical staff should focus on elderly cancer patients with low educational level, short duration of illness, impaired social isolation and activities of daily living, and carry out targeted interventions based on relevant influencing factors to promote good social cohesion for them.